Planning and management of the Community Councils of the Patía region of southwestern Colombia - Toro Chalá, Elizabeth (2023)
This article explores the planning and management processes of the community councils in the Patía region of the Cauca department, located in the southwest of Colombia. The research adopts a hermeneutic-historical epistemological approach, employing documentary analysis techniques and group interviews to understand the situations and accomplishments of community management through the narratives, experiences, and stories of the community councils. To enhance data complementarity, three investigative techniques are triangulated: field observations recorded in diaries, interviews, and documentary research. The results are linked to the Colombian State as a guiding framework to strengthen cultural identity, collective territory, and economic and social development, aiming to guarantee rights and equal opportunities through ethno-development plans. Meanwhile, the community councils, guided by their worldview, embrace the life plan for sustainability, positioning themselves as guardians of territorial protection and defense. Through their community organization, they preserve their own agroecological practices, which contribute to the preservation and revival of ancestral knowledge related to the sustainable development goals.